THE ROLE OF IMMUNOGOHISTOCHEMICAL STUDY METHODS IN THE DIAGNOSIS OF PROSTATIC INTRAEPITELIAL NEOPLASIA - Melnychuk, M.P. (World of Medicine and Biology, 2021)
The article deals with the problem of diagnosing prostatic intraepithelial neoplasia as a precancerous process. Data on the expression of proliferation markers (Ki-67) and invasion (p63) in patients with prostatic intraepithelial neoplasia of high and low degrees are analyzed. The total of 93 patients with prostatic intraepithelial neoplasia who were studied for Ki-67 and p63 expression were examined. High-grade prostatic intraepithelial neoplasia has been shown to have a greater potential for proliferation and invasive growth than low-grade prostatic intraepithelial neoplasia. In patients with high-grade prostatic intraepithelial neoplasia, more intensive expression of Ki-67 was observed by 24 % more frequently, and by 11 % pronounced expression of Ki-67 than in patients with low-grade prostatic intraepithelial neoplasia. P63 expression was higher in cases of low-grade prostatic intraepithelial neoplasia. In patients with low-grade prostatic intraepithelial neoplasia, intense p63 expression was by 25 % more common and pronounced p63 expression was by 14 % more common. The data suggest the need for in-depth examination of patients with high-grade prostatic intraepithelial neoplasia to prevent malignancy.